Regeneration of sodium alanate studied by powder in situ neutron and synchrotron X-ray diffraction - Humphries, Terry; Makepeace, J.; Hino, S.; David, W.; Hauback, B. (Royal Society of Chemistry, 2014)
The regeneration pathway of sodium alanate has been studied in detail by in situ synchrotron powder X-ray diffraction (SR-XRD) and powder neutron diffraction (PND). Rietveld refinement of the data has accurately determined the composition of all crystalline phases during the reaction process and shows definitively that Al initially reacts with NaH to form Na3AlH6, followed by the formation of NaAlH4 (before the total consumption of NaH) in two indiscrete reactions. During hydrogenation, an expansion of 0.6% of the Na3AlH6 unit cell is observed indicating towards the inclusion of Ti within the crystal lattice. This study promotes the recent development of next-generation sample holders and detectors that now enable the in situ diffraction measurement of hydrogen storage materials under relatively high gas pressures (>100 bar) and temperatures. This journal is